Financial and Legal Instruments for Promoting the Implementation of Sustainable Development Policy of the State (States, Region) - Жуковська, Аліна Юріївна; Жуковська, А. Ю.; Жуковская, Алина Юрьевна; Zhukovska, Alina Yu.; Желюк, Тетяна Леонтіївна; Желюк, Т. Л.; Желюк, Татьяна Леонтиевна; Zheliuk, Tetiana L.; Жук, Інна Іванівна; Жук, І. І.; Жук, Инна Ивановна; Zhuk, Inna I.; et al. (Allied Business Academies publishing, 2021)
Financial and legal instruments for promoting the implementation of sustainable development policy of the state (states, regions) require a detailed study of the application of financial and legal instruments for the implementation of the Global Sustainable Development Goals by 2030. The EU financial instruments provide funding for the goals and policies of sustainable development of the state or the region through the involvement of budgetary and private financial resources. The purpose of the research is to analyze the existing practice of promoting the implementation of sustainable development policy of the state (states, regions) in the EU countries through the use of financial and legal instruments in order to provide investors with economic returns in accordance with probable risks, while promoting sustainable development goals. The research methods are as follows: comparative analysis; statistical analysis; systematization, generalization. Results. Financial and legal instruments are measures of financial and legal support provided on an additional basis from the budget in order to promote the implementation of the policy of sustainable development of the state. It has been established that the sustainable development goals, namely: 1, 2, 4, 5, 10, 11, 16 and 17 are connected with the fewest of financial and legal instruments. Sustainable and green bonds that best contribute to objectives 7 (Affordable and Clean Energy), 11 (Sustainable Urban and Community Development) and 13 (Climate Change Mitigation) have been identified as perspective and promising financial and legal instruments. The financial and legal instruments towards supporting small and medium-sized enterprises, research and innovation and a low-carbon economy are the most popular in the EU. As a result of the research conducted, it has been found that financial and legal instruments towards promoting the implementation of sustainable development policy direct financial resources to the implementation of certain goals, thereby forming a gap in the implementation of the Global Sustainable Development Goals by 2030. It has been also revealed that during the programming period, financial and legal instruments were installed exceptionally slowly; as a result, by the end of 2016, less than 5 percent was actually invested than planned.

Фінансово-правові інструменти сприяння реалізації політики сталого розвитку держави (держав, регіонів) вимагають детального вивчення застосування фінансово-правових інструментів для реалізації Глобальних цілей сталого розвитку до 2030 року. Фінансові інструменти ЄС забезпечують фінансування цілей та політики сталого розвитку держави чи регіону шляхом залучення бюджетних та приватних фінансових ресурсів. Метою дослідження є аналіз існуючої практики сприяння реалізації політики сталого розвитку держави (держав, регіонів) у країнах ЄС шляхом використання фінансово-правових інструментів з метою надання інвесторам економічної віддачі відповідно до ймовірних ризиків, сприяючи досягненню цілей сталого розвитку. Методами дослідження є: порівняльний аналіз; статистичний аналіз; систематизація, узагальнення. Результати. Фінансово-правові інструменти – це заходи фінансово-правового забезпечення, що надаються на додатковій основі з бюджету з метою сприяння реалізації політики сталого розвитку держави. Встановлено, що цілі сталого розвитку, а саме: 1, 2, 4, 5, 10, 11, 16 та 17 пов’язані з найменшою кількістю фінансово-правових інструментів. Стійкі та зелені облігації, які найкращим чином сприяють досягненню цілей 7 (Доступна та чиста енергія), 11 (Сталий розвиток міст і громад) та 13 (Пом’якшення наслідків зміни клімату), були визначені як перспективні та багатообіцяючі фінансові та юридичні інструменти. Фінансово-правові інструменти підтримки малих і середніх підприємств, досліджень та інновацій та низьковуглецевої економіки є найпопулярнішими в ЄС. У результаті проведеного дослідження встановлено, що фінансово-правові інструменти сприяння реалізації політики сталого розвитку спрямовують фінансові ресурси на реалізацію певних цілей, утворюючи тим самим прогалину в реалізації Глобальних цілей сталого розвитку до 2030 року. Також було виявлено, що протягом програмного періоду фінансово-правові інструменти встановлювалися надзвичайно повільно; як наслідок, до кінця 2016 року фактично було інвестовано менше 5 відсотків, ніж планувалося.
Zhukovska A. Financial and Legal Instruments for Promoting the Implementation of Sustainable Development Policy of the State (States, Region) / A. Zhukovska, T. Zheliuk, …, K. Vozniakovska // Journal of Management Information and Decision Sciencesthis link is disabled. – Vol. 24. – Iss. 3. - Allied Business Academies publishing, 2021. - Р. 1–16.
Keywords: sustainable development; sustainable development goals; programming period; operational programs; green, social and sustainable bonds; financial and legal instruments; the EU countries; European Commission; сталий розвиток; цілі сталого розвитку; період програмування; оперативні програми; зелені, соціальні та стійкі облігації; фінансово-правові інструменти; країни ЄС; Європейська комісія; Research Subject Categories::LAW/JURISPRUDENCE